2005
DOI: 10.1186/1742-4755-2-9
|View full text |Cite
|
Sign up to set email alerts
|

"Near-miss" obstetric events and maternal deaths in Sagamu, Nigeria: a retrospective study

Abstract: Aim: To determine the frequency of near-miss (severe acute maternal morbidity) and the nature of near-miss events, and comparatively analysed near-miss morbidities and maternal deaths among pregnant women managed over a 3-year period in a Nigerian tertiary centre. Methods:Retrospective facility-based review of cases of near-miss and maternal death which occurred between 1 January 2002 and 31 December 2004. Near-miss case definition was based on validated disease-specific criteria, comprising of five diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
103
10
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(151 citation statements)
references
References 16 publications
(22 reference statements)
31
103
10
7
Order By: Relevance
“…Our results are comparable to the incidence of 0.8-8.23 % reported for hospitals in resource poor settings in the WHO systematic review of severe acute maternal morbidity [3]. It was lower than that observed in a Nigerian study , where almost one in six women suffered life-threatening emergencies [4]. A much lower incidence of severe obstetric conditions has been reported from European countries and United Nation indicating an inverse association between incidences of emergency obstetric cases with the development status of a country [5].…”
Section: Discussionsupporting
confidence: 38%
“…Our results are comparable to the incidence of 0.8-8.23 % reported for hospitals in resource poor settings in the WHO systematic review of severe acute maternal morbidity [3]. It was lower than that observed in a Nigerian study , where almost one in six women suffered life-threatening emergencies [4]. A much lower incidence of severe obstetric conditions has been reported from European countries and United Nation indicating an inverse association between incidences of emergency obstetric cases with the development status of a country [5].…”
Section: Discussionsupporting
confidence: 38%
“…Prevalence of MNM was evaluated and for each group of primary obstetric complication leading to MNM, maternal morbidity was compared to maternal mortality, and prevalence ratio, case fatality ratio (CFR), and mortality index (MI) were calculated [8] …”
Section: Methodsmentioning
confidence: 99%
“…[169][170][171][172] Studies from different parts of the world, including the UK, show a higher risk of mortality among women who do not receive adequate antenatal care. 156,169,171,173 Although there is a debate about the role of antenatal care in preventing maternal deaths caused by acute conditions that emerge close to the time of delivery, its role in identifying pregnant women at high risk (such as women with hypertensive disorders, medical comorbidities, anaemia and infections) and lowering their risk of mortality is widely accepted. 174 Confidential enquiries into maternal deaths in the UK have identified that a number of women who die during or after pregnancy are substance misusers, although the association with maternal death has not been formally quantified before now.…”
Section: Conclusion and Implications For Policy And Practicementioning
confidence: 99%